On-shelf nutrient trapping enhances the fertility of the southern Benguela upwelling system - Flynn, Raquel (Department of Oceanography, 2020)
The southern Benguela upwelling system (SBUS), located off the southwest coast of Africa, supports high rates of primary productivity that sustain important commercial fisheries. The exceptional fertility of this system is reportedly fuelled not only by upwelled nutrients, but also by nutrients regenerated on the broad and shallow continental shelf. We present the first nitrate nitrogen (N) and oxygen (O) isotope data (δ15N and δ18O, respectively) from the SBUS, generated for samples collected along four hydrographic lines in February (summer) and May (early winter) of 2017. During summer upwelling, a decrease in nitrate δ 18O on the shelf reveals that on average, 30% of the subsurface nutrients derive from in situ remineralization of sinking phytoplankton biomass. In the more quiescence winter, an average of 35% of the on-shelf nitrate is regenerated, with the signal propagating further westward along the mid-shelf region such that the total regenerated nitrate burden is greater during this season. In both seasons, a shoreward increase in subsurface nitrate δ 15N and decrease in N* (i.e., total dissolved nitrogen - 16 x phosphate + 2.9) suggests N loss to benthic denitrification coincident with the on-shelf remineralization, which implies that an even higher quantity of nitrate is regenerated than we calculate. Our data show that remineralized nutrients get trapped on the SBUS shelf in summer and early winter, enhancing the nutrient pool that can be upwelled to support surface productivity and decreasing bottom water oxygen concentrations. The proposed mechanism for this “nutrient trapping” involves upwelled nutrients being removed from surface waters and converted into organic biomass that is sequestered and remineralized on the shelf while the now nutrient-deplete surface waters are advected offshore by Ekman transport. This process is aided by a number of equatorward-flowing fronts that impede the lateral exchange of waters in the upper 200 m of the water column, increasing their residence time on the shelf. The extent to which remineralized nutrients are trapped on the SBUS shelf has implications for bottom water hypoxia. Trapped nutrients will be supplied to the surface during upwelling, supporting high rates of primary productivity and a large sinking biomass flux. The subsequent on-shelf remineralization of this organic matter has the potential to further decrease already-low bottom water oxygen concentrations.